Low water treatability efficiency of wildfire-induced dissolved organic matter and disinfection by-product precursors - UZUN, HABİBULLAH (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Wildfire could alter both the quantity and composition of terrestrial organic matter exported into source water, and water treatability of fire-impacted dissolved organic matter (DOM) could be different from its unburned counterpart. Currently, there is no standard protocol to treat wildfire-impacted source water. To identify the best treatment practices in handling post-fire runoffs, we conducted a systematic controlled study using leachates of unburned white fir (Abies concolor) and Ponderosa pine (Pinus ponderosa) and black and white ashes (collected immediately and one year after the 2013 Rim Fire, California) to evaluate coagulation and oxidation strategies for controlling disinfection byproducts (DBPs) formation. Results showed that the efficiency (%) of alum coagulation in removing dissolved organic carbon and nitrogen followed the order of litter > ash immediately after the fire > ash one year after the fire. Alum coagulation was less effectiveness in removing DOM and DBP precursors in ash leachates, compared to litter leachates. This may be attributed to the loss of side chains and the decrease of DOM molecular weight during the wildfire, thus inducing lower removal efficiency of the DOM and DBP precursors during the alum coagulation. Considering use of brominated flame retardants by firefighters, the addition of bromide (Br-) (100 mu g/L) greatly increased the formation of haloacetonitriles by chlorine, and this increase was relatively lower in ash leachates. The influence of reaction time and pH on DOM reactivity was similar among the leachates of litter and ash samples. Our results show that alum coagulation followed by chloramination at alkaline pH is an effective strategy for reducing post-fire DBP formation in drinking water. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: Wildfire; Water treatability; Alum coagulation; Disinfection byproducts; Bromine incorporation; pH; MATRIX REGIONAL-INTEGRATION; DRINKING-WATER; FLUORESCENCE EXCITATION; PARAFAC COMPONENTS; QUANTIFY SPECTRA; FIRE SEVERITY; WASTE-WATER; CHLORINATION; QUALITY; FOREST